Contribution of Genetic Background and Data Collection on Adverse Events of Anti–human Immunodeficiency Virus (HIV) Drugs (D:A:D) Clinical Risk Score to Chronic Kidney Disease in Swiss HIV-infected Persons With Normal Baseline Estimated Glomerular Filtration Rate. (6th April 2019) - Dietrich, Léna G; Barceló, Catalina; Thorball, Christian W; Ryom, Lene; Burkhalter, Felix; Hasse, Barbara; Furrer, Hansjakob; Weisser, Maja; Steffen, Ana; Bernasconi, Enos; Cavassini, Matthias; de Seigneux, Sophie; et al.
Abstract: Background: In human immunodeficiency virus (HIV), the relative contribution of genetic background, clinical risk factors, and antiretrovirals to chronic kidney disease (CKD) is unknown. Methods: We applied a case-control design and performed genome-wide genotyping in white Swiss HIV Cohort participants with normal baseline estimated glomerular filtration rate (eGFR >90 mL/minute/1.73 m 2 ). Univariable and multivariable CKD odds ratios (ORs) were calculated based on the Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) score, which summarizes clinical CKD risk factors, and a polygenic risk score that summarizes genetic information from 86 613 single-nucleotide polymorphisms. Results: We included 743 cases with confirmed eGFR drop to <60 mL/minute/1.73 m 2 (n = 144) or ≥25% eGFR drop to <90 mL/minute/1.73 m 2 (n = 599), and 322 controls (eGFR drop <15%). Polygenic risk score and D:A:D score contributed to CKD. In multivariable analysis, CKD ORs were 2.13 (95% confidence interval [CI], 1.55–2.97) in participants in the fourth (most unfavorable) vs first (most favorable) genetic score quartile; 1.94 (95% CI, 1.37–2.65) in the fourth vs first D:A:D score quartile; and 2.98 (95% CI, 2.02–4.66), 1.70 (95% CI, 1.29–2.29), and 1.83 (95% CI, 1.45–2.40), per 5 years of exposure to atazanavir/ritonavir, lopinavir/ritonavir, and tenofovir disoproxil fumarate, respectively. Participants in the first genetic score quartile had no increased CKD risk, even if they were in the fourth D:A:D score quartile. Conclusions: Genetic score increased CKD risk similar to clinical D:A:D score and potentially nephrotoxic antiretrovirals. Irrespective of D:A:D score, individuals with the most favorable genetic background may be protected against CKD. Abstract : A polygenic risk score, summarizing information from >86 000 single-nucleotide polymorphisms, predicts chronic kidney disease risk in Swiss HIV-infected persons. The genetic effect size is similar to the clinical D:A:D risk score and similar to exposure to potentially nephrotoxic antiretrovirals.